AN ALTERNATIVE APPROACH TO DETERMINING THE RATE OF RUNOFF OF UNSTUDIED RIVERS (THE AMUR RIVER BASIN IN THE TRANSBAIKAL KRAI AS A STUDY CASE) - Dmitry A. Shalikovskiy; Valeriy N. Zaslonovskiy; Andrey V. Shalikovskiy (Водное хозяйство России: проблемы, технологии, управление)
The article presents an approach to determining the flow rate of unexplored rivers depending on their order according to A. Scheidegger and the corresponding zoning. It is shown that the use of a single dependence of the flow rate on the river order gives significant errors for small streams. This is because of the fact that approximation function of the entire data file actually reflects regularities only for hydrological stations with great values of the runoff norm. For the territory of the Amur Basin within the Transbaikal cray, five regions have been identified, within which the dependences of the flow rate of small and medium rivers have values of the correlation coefficient from 0.95 to 0.97. An additional zoning scheme for the area under consideration has also been developed, which makes it possible to simplify the determination of the order of the river. The proposed scheme of flow rate determination includes the following operations: determination of the area according to the additional scheme – calculation of the river order – determination of the area according to the main scheme – calculation of the flow rate.